Network disruption detected in BH (Bahrain) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Bahrain. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: BH-2026-0001. Severity: critical. Confidence: 65%